Effect of thymectomy and antilymphocyte serum on Mycobacterium leprae infection in mice. - Fieldsteel, A H (1975)
BALB/c mice thymectomized at 3 to 5 days of age were studied to determine if this procedure would result in enhanced susceptibility to infection with Mycobacterium leprae and, if so, whether or not administration of antilymphocyte serum would further increase this susceptibility. The plateau for growth in the footpads of intact mice occurred 4 months after inoculation, whereas in the thymectomized and thymetocomized plus antilymphocyte serum-treated groups the plateau occurred between months 11 and 12 after inoculation. Thymectomy resulted in at least a 10-fold increase in the number of M. leprae found in the footpads. Antilymphocyte serum did not appear to further enhance the M. leprae infection in the thymectomized mice. Although growth of M. leprae in the testes of both intact and thymectomized mice was erratic, the number of organisms reached a higher ceiling in the thymectomized groups. M. leprae harvested from all groups was passaged into intact mice at various intervals after inoculation to test for viability. Viable M. leprae were found at all intervals tested including 22 months after infection in the intact mice, suggesting that a chronic infection occurred that probably lasted during the entire life of the animals.